Pengembangan Instrumen Asesmen Kompetensi Minimum Numerasi pada Domain Data dan Ketidakpastian untuk Siswa SMP - Hayati, Rohimatul; Nindiasari, Hepsi (Universitas Veteran Bangun Nusantara, 2024)
This study aims to produce valid and practical minimum competency assessment instrument. This study uses the research and development (R&D) of the ADDIE model. The subjects of this study consisted of 32 students in grades VIII SMP Negeri 1 Anyar. The instruments used consisted of expert validation sheets, student response questionnaires, and minimum competency assessment instrument. The data analysis techniques in this study are quantitative analysis and qualitative analysis. Based on the results of research and development of the minimum numeracy competency assessment instrument in the uncertainty and data domain for junior high schools, it was concluded that two questions were very valid, five questions were valid, and one question was invalid. Based on the power of differentiation, invalid questions can be revised or do not need to be used. Meanwhile, the results of the student response questionnaire were obtained by 84%, meaning that it included very practical criteria with 83% for the content aspect, 80% for the construction aspect, and 90% for the language aspect. Thus, this minimum competency assessment instrument can be used in mathematics learning.